Using the Hand-Sewn Purse-String Stapled Anastomotic Technique for Minimally Invasive Ivor Lewis Esophagectomy - Zhan, Bicheng; Chen, Jian; Du, Shaoming; Xiong, Yanzheng; Liu, Jian (The Thoracic and Cardiovascular Surgeon, 2019)
Background Minimally invasive Ivor Lewis esophagectomy (MIILE) is increasingly being used in the treatment of middle or lower esophageal cancer. Hand-sewn purse-string stapled anastomosis is a classic approach in open esophagectomy. However, this procedure is technically difficult under thoracoscopy. The hardest part is delivering the anvil into the esophageal stump. Herein, we report an approach to performing this step under thoracoscopy.Methods A total of 257 consecutive patients who underwent MIILE between April 2013 and July 2017 were analyzed retrospectively. The operator hand sewed the purse string using silk thread under thoracoscopy, and the 25-mm circular stapler was passed through the anterior axillary line at the fourth intercostal space to finish the side-to-end gastroesophageal anastomosis. Patient demographics, intraoperative data, postoperative complications were evaluated.Results The mean operative time, thoracoscopy time, and anvil fixation time was 307.0 ± 34.3, 155.4 ± 21.5, and 7.1 ± 1.6 minute, respectively. The anastomotic leak and anastomotic stricture occurred in 6.6% (17 of 257) and 3.9% (10 of 257) of patients, respectively. There was no intraoperative death; one case was death of acute respiratory distress syndrome (ARDS) for conduit gastric leakage on the 21st postoperative day.Conclusion Using the hand-sewn purse-string stapled anastomotic technique for MIILE is feasible and relatively safe in patients with middle or lower esophageal cancer.
Keywords: minimally invasive esophagectomy; esophageal cancer; esophagogastric anastomosis; purse-string stapled anastomotic technique